Penerapan Strategi Pemasaran Wisata Kolam Pancing “Cak Rul Fishing” Dalam Perspektif Marketing 4.0 - Arif Zunaidi; Risa Rahmah (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2021)
The world saw a reduction in the phenomenon of environmental effects during this year's Covid19 pandemic. So far, fishing pond tours have already been classified as quiet tour packages because their activities depend on simply sitting around and waiting for fish to become interwoven on the fishing line. Visitors have been few, although most people are aware of its existence, apart from those who share interests. The fishing pond tour